2008
DOI: 10.1111/j.1748-1090.2007.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of construction noise on behaviour of and exhibit use by Snow leopards Uncia uncia at Basel zoo

Abstract: Noise caused by human activities can cause stress in animals. We examined whether noise from construction sites affects the behaviour of and exhibit use by three Snow leopards Uncia uncia at Basel zoo. The behaviour and location of the animals were recorded at 1 minute intervals, using the instantaneous scan sampling method over a period of 216 hours (104 hours on noisy days and 112 hours on quiet days). The animals differed individually in their responses to the construction noise. On noisy days, the Snow leo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 8 publications
4
20
0
Order By: Relevance
“…Similar findings have been reported in tamarins ( Saguinus spp ., Moodie and Chamove, ] and leopard cats [ Prionailurus bengalensis , Carlstead et al, ]. This is also in accordance with the findings of Sulser et al [] who found construction noise resulted in less walking, more resting, and more time spent in the rear of the exhibit, where both visibility and volume were decreased, in captive snow leopards ( U. uncia ).…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings have been reported in tamarins ( Saguinus spp ., Moodie and Chamove, ] and leopard cats [ Prionailurus bengalensis , Carlstead et al, ]. This is also in accordance with the findings of Sulser et al [] who found construction noise resulted in less walking, more resting, and more time spent in the rear of the exhibit, where both visibility and volume were decreased, in captive snow leopards ( U. uncia ).…”
Section: Discussionsupporting
confidence: 84%
“…Behavioural and conservation aspects of zoo animals are examined by students and scientists at the University of Basel (e.g. Zschokke & Baur, 2002;Hegetschweiler et al, 2003;Steck et al, 2006;Sulser et al, 2008).…”
Section: From the Idea To The Surveymentioning
confidence: 99%
“…Little is known about the extent to which captive animals experience stress and anxiety due to dynamite detonations that may occur during this kind of work (giant pandas, 1 snow leopards 2 ). Stress is known to have many physiological effects in different organ systems in the body, such as the immune system, the hormonal system and the gastrointestinal system.…”
mentioning
confidence: 99%